"Regular Progressive Work Occupies My Mind Best": Needlework as a Source of Entertainment, Consolation and Reflection. (3rd May 2016) - Long, Bridget
Abstract: This article examines the experiences of sociable and solitary needlewomen in the long eighteenth century to reveal some of the emotional benefits derived from the act of sewing. Following Rosenwein's theory of "emotional communities, " this article considers how needlework was centered in a number of emotional groups sited within the domestic sphere. The article will argue that the home was the place for "emotional sewing" and that both sociable and solitary sewing provided sources of emotional support. It considers evidence from eighteenth-century women's diaries and reminiscences, including those written by Sarah Hurst, Anna Larpent, Catherine Hutton, and Gertrude Savile, which provides a rare opportunity to consider feelings about a skill traditionally passed from mother to daughter and frequently practiced in social groups. Despite the feeling that needlework symbolized the restricted role of eighteenth-century women, who were confined to their domestic environment while constrained by male expectations, the article suggests that the subversive side of sewing should not be ignored. Well-practiced in all needlework skills, some women may have had a different view of needlework using the hours spent sewing to focus on other concerns and negotiate time for their social, emotional, and intellectual well-being. It examines the likely difference between female and mixed groups when good cheer and merriment may have been as important as intellectual discussion and emphasizes that solitary sewing allowed time for reflection and consolation.